The EU ineffective counterterrorism strategy - Marsili, M. (Ciência 2017, 2017)
The European Union security and counter-terrorism strategy adopted after 11 September 2001 has not been effective, instead resulted in the increase of Islamist terrorist incidents. Europe has been hit by a wave of terrorist attacks, which demonstrates the limits of the Security and Defence Policy. The EU short-term strategy, tending only to hit terrorist organisations, has not produced the expected effects: attacks in Europe, rather than decreasing, have increased. Little or nothing has been done to develop a successful preventive strategy. After the early 2000s, there is hardly registered Islamic attack within the EU, due to the change in the Al-Qaeda strategy. The recrudescence recorded after 2014 coincides with the rise of ISIS.